ANALISIS KELAYAKAN FINANSIAL USAHATANI JAGUNG DI KABUPATEN LOMBOK BARAT - HERNAWATI .; PARTA TANAYA; ABUBAKAR AHMAD (Universitas Mahasaraswati Mataram, 2018)
This study aims to analyze the cost and income and financial feasibility of corn farming in West Lombok regency. This research is conducted in West Lombok regency involving 60 respondents. The research method used is descriptive method, with data analysis using cost and income analysis and RC ratio. The results shows that the production cost of corn farming is Rp 3,037,170 / Ha, with the revenue value of Rp. 9,500,313 and income received by farmers in corn cultivation amounted to Rp 6,436,143 / Ha. Financially, corn farming in West Lombok Regency is advantageous and feasible to be cultivated because it has RC ratio of more than one ratio of 3.13